Duration Model of Enterprises - Analysis of Territorial Groups - Iwona Markowicz (Institute of Economic Research (IER), 2017)
The popular term of business demography or demography of the firm denotes a relatively young area of science which focuses on the structures of cohorts of firms and the changes that undergo within these structures. As both the terms suggest, the studies use research methods traditionally applied in demographic studies. Survival analysis is increasingly used in business demography. The purpose of the present study was to build the enterprises survival models for territorial groups in Zachodniopomorskie (Poland). In the first stage the Kaplan-Meier estimator was calculated and the test to verify the similarity of the survival function for poviats was conducted. Poviats were classified into groups. Next, the tables of enterprises survival were built and the business liquidation intensity was analysed in individual groups. In this study the continuous-time non-parametric models were used: Kaplan-Meier estimator, Gehan test and duration table. Those methods were employed to model the survival time and find differences in the survival of firms in the poviats of the Zachodniopomorskie. In keeping with the above scheme five territorial groups with similar enterprises survival time models were distinguished. The study results presented in this article reveal the differentiation of enterprises survival models in the territorial groups. Five groups of poviats were distinguished. These groups, as a result of the study, have been characterized.
Keywords: C10; C14; C41; 330; model of enterprises duration; Kaplan-Meier estimator; hazard function; cohort tables of enterprises survival